KAJIAN JEMBATAN A-HALF THROUGH ARCH DENGAN SNI 1725:2016 DAN SNI 2833:2016 (STUDI KASUS JEMBATAN RUMPIANG KABUPATEN BARITO KUALA) - Chairunnisa, Nursiah; Pratiwi, Ade Yuniati; Cahyadi, Ahmad; Karim, Abdul; Nurwidayati, Ratni; Prakoso, Puguh Budi (JURNAL TEKNIK SIPIL, 2024)
The Rumpiang Bridge is a Half Through Arch type bridge in Marabahan City, Barito Kuala District. This bridge was constructed in 2003 using loading regulations based on the BMS 1992 regulations. In 2016, the government issued the bridge loading regulations SNI 1725:2016, which introduced differences in loading compared to BMS 1992. Therefore, a structural modeling of the bridge was carried out to determine its capacity using the updated loadings from SNI 1725:2016 and SNI 2833:2016. The research utilized the Midas Civil software for assistance. The assessment of the bridge's capacity was based on the deflection values experienced by the bridge. The analysis results indicated that the maximum deflection values occurred under the combination of Static Load Case 1 and Dynamic Load Case 1. For Static Load Case 1, the maximum deflection values at the center span according to BMS 1992 and SNI 1725:2016 were 47.37 cm and 47.25 cm respectively. For Dynamic Load Case 1, the maximum deflection values at the center span according to BMS 1992 and SNI 1725:2016 were 30.108 cm and 28.41 cm respectively. On the other hand, under seismic loading based on SNI 2833:2016, the displacement experienced by the bridge due to the extreme combination 1 was 13.933 mm. Based on the conducted analysis, it is evident that the loading requirements from SNI 1725:2016 yield deflection results that still meet the criteria compared to the loading requirements from BMS 1992.